Improving basic football skills through first touch training: a comprehensive study; [Mejorar las habilidades bsicas del ftbol mediante el entrenamiento del primer toque: un estudio exhaustivo] - Mohd Izwan bin Shahril, Nor Fadila binti Kasim (Tanjung Malim, 2024)
Improving basic football skills through first touch training: a comprehensive study; [Mejorar las habilidades bsicas del ftbol mediante el entrenamiento del primer toque: un estudio exhaustivo] by Mohd Izwan bin Shahril, Nor Fadila binti Kasim